Human rights, economic powerand multinational companies - Asúnsolo-Morales, Carlos R. (2023)
The main objective of this article is to identify some of the difficulties that a traditional human rights conception —as a concept that only concerns the public powers— faces in the process of economic globalization. Through a historical- sociological analysis of the human rights concept, as a modern age notion that born to impose limits to the political power, the article will attempt to highlight the exclusion of the economic powers, including the multinational corporations, thanks to the above mentioned analysis of human rights. The omission is reflected in the hegemonic globalization process that the world is experiencing, a process that generates great economic profits for the multinational corporations, but does not create the social conditions to improve the life of the majority of people. This, in turn, is causing a deficit in the protection of human rights. This situation forces us to rethink the delimitation of responsibilities in the task to ensure the protection of human rights. Therefore, the United Nations has recently made efforts to impose human rights obligations to multinational corporations.